A systematic review of drug induced ocular reactions in diabetes. Issue 2 (1st February 2000) - Hampson, J P; Harvey, J N
Abstract : AIMS: To conduct a systematic review of drug induced adverse ocular effects in diabetes to determine if this approach identified any previously unrecognised adverse drug effects; to make a preliminary assessment of the feasibility of this approach in identifying adverse drug reactions; and to assess the current accessibility of this information to prescribing physicians. METHODS: Literature search of online biomedical databases. The search strategy linked eye disorders with adverse drug reactions and diabetes. Source journals were classified as medical, pharmaceutical, diabetes related, or ophthalmological. It was determined whether the reactions identified were recorded in drug datasheets and the British National Formulary. RESULTS: 63 references fulfilled the selection criteria, of which 45 were considered to be relevant to the study. The majority of these were case reports but cross sectional surveys, case-control and cohort studies, and review articles were also identified. 61% of the reactions were not recorded in the British National Formulary and 41% were not recorded in the datasheets. 55% appeared in specialist ophthalmology journals. CONCLUSIONS: This is a feasible approach to the identification of adverse drug reactions. Adverse reactions not listed in the most commonly used reference sources were found. The majority were published in specialist ophthalmology journals which might not be seen by prescribing physicians.